Large Pelvic Hematoma after UroLift® Procedure for Treatment of BPH with Median Lobe - Max J. Roehmholdt; Dennis F. Bentley (Case Reports in Urology)
The UroLift® procedure is a minimally invasive technique used to treat benign prostatic hyperplasia (BPH) in the office or hospital setting. As of 2021, over 200,000 of these procedures have been performed, with an excellent safety profile. We present a case report of a patient who underwent the UroLift® procedure and was found to have a 16.5 cm pelvic hematoma within 16 hours. This study was done as a retrospective chart review. In addition, a comprehensive review of the literature was performed, and all relevant government and company websites were reviewed for thorough evaluation. The patient had an uncomplicated inpatient UroLift® procedure for BPH using 5 implants and was discharged from the hospital without incident. The patient presented to the emergency department with abdominal pain 16 hours after the procedure, and a 16.5 cm pelvic hematoma was found on computerized tomography (CT) scan. Since 2015, there have been 27 cases of pelvic hematoma after UroLift® reported to the United States Food and Drug Administration (FDA), and only 2 cases published in the literature. Our patient required hospital admission for 3 days and 3 units of packed red blood cells, but no surgical exploration or intervention. The procedure was technically successful as it improved the patient’s voiding and lower urinary tract symptoms (LUTS) as of 2-month follow-up. Potential etiologies include implant firing depth beyond the extent of the prostate, as well as treatment of the median lobe.